FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU SMAN 1 MOYO UTARA: SUPERVISI PENGAWAS DAN IKLIM ORGANISASI - Fibriyansari, Tiara; Rahim, Abdul; Fitriyani, Ika (Fakultas Ekonomi dan Manajemen, 2023)
This study was conducted to examine the influence of supervisory supervision and organizational climate on teacher performance at SMAN 1 Moyo Utara. The type of this study was associative. The type of data used is quantitative data in the form of respondents' responses in answering the questions given. The quantitative data used in this study was obtained directly from primary sources, namely the teachers of SMAN 1 Moyo Utara through questionnaires. The population in this study were the teachers of SMAN 1 Moyo Utara, totaling 27 people. Seeing that the population in this study is relatively small, it provides the opportunity for researchers to study all members of the population so that the sample that will be used as respondents in this study is the entire population of 27 people. The data that has been collected is processed using the SPSS application and then analyzed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination test (R2). The results of this study showed that the supervisory supervision and organizational climate had a positive and significant effect on teacher performance at SMAN 1 Moyo Utara, both partially and simultaneously. Supervisory supervision and organizational climate had a large ability to influence changes in teacher performance at SMAN 1 Moyo Utara, namely 73.2%, while the remaining 26.8% is influenced by other variables not examined in this research model, such as the leadership style, work competence, work motivation, and work discipline.